Answer: C, 2 3/5
Explanation:
- Let's start by making these fractions easily subtractable
7 1/5 = 6 6/5 (1 is equal to 5/5 so we take that from the 7 and add it to the fraction)
4 3/5 remains the same because this is what we are subtracting
7 1/5 - 4 3/5 will be subsituted for 6 6/5 - 4 3/5=? because it's equivilant
I like to break this into two parts to make it less complicated, fraction then number
- Fraction: 6/5-3/5=3/5
- Whole Number 6-4=2
- Combine back into a mixed number
This will give you the proper fraction for the result of your equation
2+3/5=2 3/5
2 3/5